Analysis Factors that Affect Preeklampsia Incident of Pregnan Women at RSUD Sultan Imaniddin Pangkalan Bun - Santa Betty; Indasah Indasah; Yenny Puspitasari (Journal for Quality in Public Health, 2020)
Preeclampsia is a hypertension caused by pregnancy that is characterized by hypertension, edema,and proteinuria after the 20 week. One of the causes of maternal death is preeclampsia. The purpose of this study was to determine the factors that influence the incidence of preeclampsia at Sultan Imanuddin Pangkalan Bun The population is 236 respondents and the sample is 148 respondents with a random sampling technique. Data collection is observation. Data analysis using logistic regression test . Based on the logistic regression test results obtained a history of significance hypertensi (0,000)., Gemelly significance (0.999)., Obesity significance (0.000). Simultaneously influenced the incidence of preeclampsia. The most influential variable was a history of hypertension with values (Exp.B: 131,238). History of hypertension (X1) obtained p value 0.000 <0.05 so there is a influence with the incidence of preeclampsia (Y) means H1 is accepted. Gemelly (X2) obtained p value 0.999> 0.05 so there is no influence with the incidence of preeclampsia (Y) means H1 is rejected. Obesity (X3) obtained p value 0.000 <0.05 so there is a influence with the incidence of preeclampsia (Y) means H1 is accepted The most dominant factor influenced the incidence of preeclampsia is a history of hypertension with a significance value of 0.000 <0.05 with (ExpB 131.238).